Ambivalence and Symbolic Dualism in the Character of Kumbakarna in the Wayang Golek Lakon “Kumbakarna Gugur”: A Narrative Analysis - Maulana, Marsel Ridky (Universitas Nusantara PGRI Kediri, 2025)
The lakon “Kumbakarna Gugur” in wayang golek highlights the moral ambivalence and symbolic dualism inherent in the character of Kumbakarna. As a warlord of the Alengka kingdom, Kumbakarna faces doubts between his loyalty to his brother Rahwana and his responsibility to the people and his country Alengka. The purpose of this research is to analyze ambivalence and symbolic dualism in Kumbakarna's character using Vladimir Propp's narrative function theory and Claude Lévi-Strauss' binary opposition. The research uses a qualitative method with a narrative analysis approach based on data from the text of the lakon and interviews with dalang wayang golek. The results showed that Kumbakarna's role as donor and villain in the narrative structure reflects a complex conflict of values. Through the binary opposition analysis approach, Kumbakarna is interpreted as a symbolic representation of the combination of virtue and vice that has significant relevance in reflecting leadership values. The moral values contained in this play such as sacrifice and responsibility become an important educational medium for the community. This research provides a new contribution to the study of wayang golek purwa as an art form that is not only entertaining but also rich in philosophical meaning.